Upaya Guru dalam Mengendalikan Kedisiplinan Belajar Siswa di Kelas V SDN Wadung Kabupaten Malang - Erlinda Cahya Fauriza; Muchtar Muchtar; Putri Mahanani; Erlinda Cahya Fauriza; Muchtar Muchtar (Universitas Negeri Malang, 2022)
Abstract: Student learning discipline is very necessary because it can facilitate the learning process in the classroom. This research aims to find out the efforts of teachers and the obstacles faced by teachers in controlling student learning discipline in class V of SDN Wadung Malang Regency. Research methods use descriptive qualitative. The data collection tools in this study used observation, interview, and documentation instruments. Data analysis uses qualitative descriptive analysis with miles and huberman models including data reduction, data presentation, and inference. The results of the study showed that the efforts made by teachers in controlling learning discipline by using classroom management through authoritarian, permissive, democratic, and pseudo-democratic approaches. Teachers also set good example examples, enforcing rules in the classroom, giving negative reinforcement and giving positive reinforcement to students. The obstacles faced by teachers in controlling student learning discipline are the teacher's reluctance to provide negative reinforcement to students. Abstrak: Kedisiplinan belajar siswa sangat diperlukan karena dapat memperlancar proses belajar di kelas. Penelitian ini bertujuan untuk mengetahui upaya guru serta kendala yang dihadapi guru dalam mengendalikan kedisiplinan belajar siswa di kelas V SDN Wadung Kabupaten Malang. Metode penelitian menggunakan kualitatif deskriptif. Alat pengumpulan data pada penelitian ini menggunakan instrument observasi, wawancara, dan dokumentasi. Analisis data menggunakan analisis deskriptif kualitatif dengan model miles dan huberman meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Hasil dari penelitian menunjukan bahwa upaya yang dilakukan guru dalam mengendalikan kedisiplinan belajar dengan menggunakan pengelolaan kelas melalui pendekatan otoriter, permisif, demokratis, dan pseudo demokratis. Guru juga memberikan contoh teladan yang baik, menegakkan peraturan di kelas, pemberian hukuman serta pemberian penghargaan kepada siswa. Kendala yang dihadapi guru dalam mengendalikan kedisiplinan belajar siswa yakni keengganan guru dalam memberikan hukuman kepada siswa.